The Effect of Applying Cooperative Integrated Reading and Composition (CIR ) Technique on Students’ Achievement in Writing Recount Text - Sara Frimaulia; Edi Suprayetno (English Lecturers and Teachers Association (ELTA), 2021)
This study aims to discover the effect of applying Cooperative Integrated Reading and Composition (CIRC) Technique on Student’s Achievement in writing Recount Text. It was conducted by using experimental research design. This population was the 80 students of SMP Negeri 1 Stabat as Sample. The samples of the research were two classes divided into two groups, experimental and control group which were chosen by using random sampling technique. The Grade VIII-B as Experimental Group was taught by using Cooperative Integrated Reading and Composition and grade VIII-A as control group was taught by using conventional teaching writing. The instrument used to collect the data was by asking the students to write a Recount text. Based on the result of the data analysis, it was concluded that using Cooperative Integrated Reading and Composition significantly affect the student’s ability in writing recount text (t-calculated > t-table, p=0.05). The using CIRC made the students write recount text grammatically that without using CIRC. The calculation of t-test is 2.38 > 1.67 with df 78 and the level of significance 0.05. It means that the using CIRC has significant effect on writing recount text. Keywords: Experimental Research, Cooperative Integrated Reading And Composition (CIRC) Technique, Writing Achievement, Recount Text.